An investigation of radiation dose to patient's eye lens and skin during neuro-interventional radiology procedures / Mohammad Javad Safari - Mohammad Javad , Safari (2016)
X-ray guided interventional procedure is a common diagnostic and/or treatment modality for various vascular and cardiac diseases. Advanced technology has enabled interventional radiologists in performing more complex neuro-radiology procedures, resulting in concomitant increase in radiation dose to the patients. The main contributions of this thesis were firstly, characterisation of the MOSkin detector in kilovoltage photon beams and testing its suitability for in-vivo patient’s dose measurements during interventional radiology procedures. Secondly, a comprehensive evaluation of the exposure parameters contributions on patient’s dose during neurointerventional procedures was performed. It was found that the lateral x-ray tube contributed considerably high radiation dose to patient’s eye lens. This led to the design and fabrication of a novel type of eye lens protector for those procedures that patient’s eye is repeatedly positioned within the lateral tube exposure field, where the applying of collimation on lateral beam is not possible. The eye lens protector was designed to be placed within the x-ray field of view, attenuating the direct beam from the lateral x-ray tube while being sufficiently radiolucent not to perturb the radiological image and the interventional procedure. Finally, a new type of an anthropomorphic head phantom was fabricated with more options for dosimeter placement and more similar tissue substitute materials to actual human eye, in order to evaluate the dose delivered to the patient’s eye lens during a clinical neuro-interventional procedure. The MOSkin detector has been proven to be a reliable and suitable dosimetry system for the measurement of the radiation dose in kilovoltage photon beams and has been successfully utilised during 35 clinical neuro-interventional procedures to evaluate the radiation dose received by the patients’ eye lenses. This study revealed that among the 35 patients, the left outer canthus regions of 8 patients and left eyelid region of one iv patient were found to receive higher dose than the recommended threshold dose for cataract formation (500 mGy). Based on the study of the contribution of exposure parameters on patient’s dose, it is recommended that the judicial use of acquisition imaging techniques and the use of the lateral x-ray tube particularly in the anterior-oblique orientation, in order to reduce the patient’s eye lens dose during neuro-interventional procedures. In the situation where the application of physical collimation on lateral tube beam is not possible, the novel eye protector layer may be used to attenuate the direct radiation beam to the patient’s eye lens. This work showed that for a simulated aneurysm procedure this protector reduced the maximum radiation dose received by the eye lens and eyelid up to 62.1% and 23.3%, respectively. The eye protector also had negligible effects on the exposure parameters (by a maximum of 8% for the tube current-time product of the DSA (2 frame per second) imaging mode) and image quality (increases the fluoroscopy image pixel value up to 4.7% ± 0.6%). Lastly, the fabricated anthropomorphic phantom has been proved to be a suitable tissue-mimicking medium for the evaluation of the radiation dose received by the patient’s eye lens during clinical diagnostic procedures.